2023
DOI: 10.1039/d3tb01255g
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidase mimics of platinum-group metals for in vitro diagnostics: opportunities and challenges

Weiwei Gao,
Hannah Eastwood,
Xiaohu Xia

Abstract: Platinum-group metal (PGM) nanostructures with peroxidase-like catalytic activities (i.e., peroxidase mimics) have been actively developed and applied to in vitro diagnostics in recent years. This article provides our viewpoints on...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
(115 reference statements)
0
3
0
Order By: Relevance
“…33 In HRP, the active site heme is buried deep in the polypeptide macromolecules, which forms an insulating layer and eventually impedes direct electron transfer between the enzyme and electrode. 34,35 However, freely diffusing electron transfer mediators, such as hydroquinone, can shuttle electrons between the active site of the enzyme and the electrode surface during the electro-catalytic reaction between HRP and H 2 O 2 . 36 Hence, to elaborate on the role of the mediator, the electro-catalytic property of HRP-modified OCDs (OCDs@HRP) over PNP SPE (SPE-PNPs-OCDs@HRP) was evaluated by cyclic voltammetry in the presence of H 2 O 2 with and without redox mediator HQ (Fig S5, ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…33 In HRP, the active site heme is buried deep in the polypeptide macromolecules, which forms an insulating layer and eventually impedes direct electron transfer between the enzyme and electrode. 34,35 However, freely diffusing electron transfer mediators, such as hydroquinone, can shuttle electrons between the active site of the enzyme and the electrode surface during the electro-catalytic reaction between HRP and H 2 O 2 . 36 Hence, to elaborate on the role of the mediator, the electro-catalytic property of HRP-modified OCDs (OCDs@HRP) over PNP SPE (SPE-PNPs-OCDs@HRP) was evaluated by cyclic voltammetry in the presence of H 2 O 2 with and without redox mediator HQ (Fig S5, ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…[2a,5] Because peroxidases are responsible for the production of detection signal, they greatly determine the performance of a diagnostic kit, including detection sensitivity and reproducibility. [6] Nevertheless, the inherent drawbacks of peroxidases, such as poor stability, low catalytic efficiency, and high cost of isolation and purification, [4,7] significantly restrict further advancement of associated diagnostic technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Among various peroxidase mimics, those made of platinumgroup metals (e. g., Pd, Pt, Ir, and Rh) have drawn increasing attention because of their outstanding catalytic efficiencies. [6,12] In a recent study, we have systematically compared the catalytic efficiencies of peroxidase mimics made of various platinumgroup metals. [13] We found that Ir is the most catalytically active one among all other platinum-group metals.…”
Section: Introductionmentioning
confidence: 99%